(untitled) (Journal of Plant Disease Sciences, 2023)
India has long grown safflower (Carthamus tinctorius L.) as a rainfed crop, and it currently leads the world in both safflower area and production. Diseases are significant biotic restrictions in the production of safflower. Safflower wilt, caused by Fusarium oxysporum f. sp. carthami, is the most severe disease of safflower, resulting in significant yield losses. In the current investigation, four novel new fungicides and two bio-agents were tested in vitro against Fusarium oxysporum f. sp. carthami. Fluxapyroxad 333 G/L FS inhibited mycelial development the most (87.22%), followed by Tebuconazole 5.4% w/w FS (81.67%). In terms of bioagents, biopolymer-based Trichoderma harzianum inhibited mycelial growth the most (70.00%), followed by Trichoderma harzianum Th4d WP (38.89%). In vivo testing of novel fungicide compounds and bio-agents found that Fluxapyroxad 333 G/L FS achieved 63.63 percent wilt disease control, followed by Tebuconazole 5.4% w/w FS 54.55%.Biopolymer-based Trichoderma harzianum demonstrated 36.36 percent wilt control, while Trichoderma harzianum Th4d WP had the lowest disease control rate(27.27%).